The Effects of Price Risk on Housing Demand: Empirical Evidence from U.S. Markets - Han, Lu (Review of Financial Studies, 2010)
This article examines how price risk affects housing demand. It identifies two relevant channels: a financial risk effect that reduces demand, and a hedging effect that increases demand since current homes may hedge future housing costs. The latter dominates when hedging incentives are strong, namely when the likelihood of moving up the housing ladder is high and the tendency to move across markets is low. For households with weak hedging incentives, the article finds negative effects of price risk on the timing and size of home purchases, but positive effects for households with strong hedging incentives. The Author 2010. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oxfordjournals.org., Oxford University Press.